Handbook of Heterogeneous Catalysis 2008
DOI: 10.1002/9783527610044.hetcat0082
|View full text |Cite
|
Sign up to set email alerts
|

Transient Catalytic Studies

Abstract: The Importance of Transient Catalytic StudiesThe concept of using transient operations dates back to the late 1930s and the preliminary investigations conducted by Wagner and Hauffe [1,2]. Later, during the 1960s, Tamaru contributed substantially to this field in heterogeneous catalysis, in particular, by the use of the method of transient response [3] and by introducing the isotopic labeling technique [4]. Since then, transient methods have become standard tools for unraveling heterogeneously catalyzed reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 190 publications
0
2
0
Order By: Relevance
“…It was observed that the porosity gradually decreased in the first three samples. In a similar situation, Lei et al synthesised polypropylene/Cloisite Na + and polypropylene/Cloisite 15A composites in their study and analysed SEM images [11]. However, since these agglomerations are not symmetrical and randomly distributed in the matrix, it was observed that secondary structures were not formed and information about the size of the aggregates could not be obtained.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the porosity gradually decreased in the first three samples. In a similar situation, Lei et al synthesised polypropylene/Cloisite Na + and polypropylene/Cloisite 15A composites in their study and analysed SEM images [11]. However, since these agglomerations are not symmetrical and randomly distributed in the matrix, it was observed that secondary structures were not formed and information about the size of the aggregates could not be obtained.…”
Section: Resultsmentioning
confidence: 99%
“…We point out that the Review discusses numerous characterization tools (e.g., X-ray and neutron diffraction, X-ray spectroscopy, and vibrational spectroscopies), and the reader will benefit from a basic understanding of these commonly used techniques. We recommend the interested reader to introductory literature regarding these various techniques. …”
Section: Introductionmentioning
confidence: 99%